The health & wealth gospel and religious motivation - Lee, Joshua D. Y. (2015)
A study was conducted on 65 Protestant Christian participants to investigate the relationship between religious motivation and belief in the Health & Wealth gospel. Participants who identified more with the Health & Wealth gospel were more extrinsically motivated, especially in the area of personal benefits. Participants who identified less with the Health & Wealth gospel were shown to be more intrinsically motivated as well as more introjectedly regulated. Adherence to the Health & Wealth gospel, through membership in a Health & Wealth church or identification with doctrine, resulted in significantly lower levels of church commitment in areas such as outreach attendance, private Bible reading and giving to religious causes. Lastly, adherents of Health & Wealth gospel churches report a higher level of education compared to their non-Health & Wealth counterparts.